Interference in immediate spatial memory. - Smyth, Mary M.; Scholey, Keith A. (Memory & Cognition, 1994)
It has been suggested that maintenance in visuospatial immediate memory involves implicit motor processes that are analogous to the articulatory loop in verbal memory. An alternative account, which is explored here, is that maintenance is based on shifts of spatial attention. In four experiments, subjects recalled spatial memory span items after an interval, and in a fifth experiment, digit span was recalled after an interval. The tasks carried out during the interval included touching visual targets, repeating heard words, listening to tones from spatially separated locations, pointing to these tones, pointing to visual targets, and categorizing spatial targets as being from the left or right. Spatial span recall was impaired if subjects saw visual targets or heard tones, and this impairment was increased if either a motor response or a categorical response was made. Repeating words heard in different spatial locations did not impair recall, but reading visually presented words did interfere. For digit span only, the tasks involving a verbal response impaired recall. The results are interpreted within a framework in which active spatial attention is involved in maintaining spatial items in order in memory, and is interfered with by any task (visual, auditory, perceptual, motor) that also makes demands on spatial attention. Reprinted by permission of the publisher.